INTERACTIVE GREEN MARKETING APPROACHES - Zinchenko, Olha; Smyrnova, Tetyana (Current Problems of Sustainable Development, 2026)
The article examines the essence, features, and current development trends of interactive methods and approaches of green marketing in the context of digital transformation of the economy and the spread of the sustainable development concept. It is substantiated that green marketing is an important tool for the formation of environmentally responsible business, promotion of conscious consumption, and enhancement of enterprise competitiveness. It is determined that modern interactive green marketing is based on two-way communication between enterprises and consumers, the use of digital platforms, social networks, personalized communications, and innovative technologies. The main interactive methods of green marketing are systematized, including interactive communication, content-interactive, personalized, socially oriented, digital-analytical, and gamification approaches. Their role in shaping environmental awareness of consumers, developing long-term customer relationships, and involving audiences in environmental initiatives of enterprises is investigated. Particular attention is paid to the use of social networks, user-generated content, CRM systems, web analytics, artificial intelligence technologies, and digital consumer interaction platforms. The main problems of implementing interactive green marketing are identified, including the insufficient level of environmental awareness among certain groups of consumers, the risks of greenwashing, and high competition in the digital environment. The prospects for the development of interactive green marketing approaches related to further business digitalization, personalization of marketing communications, and integration of innovative technologies into the processes of environmentally responsible consumption formation are substantiated.
Keywords: green marketing; interactive marketing; sustainable development; conscious consumption; digital communications; marketing personalization; ecological brand